Proces zarządzania ryzykiem operacyjnym w banku - Lisowski, Mariusz (Risk management in banks, 2008)
This article presents the basic elements of risk management in banks. At the beginning, the factors in the financial markets are described. This article explains select stages and actions of management operational risk in banks. It also contains information about instruments of banking controlling which are used in commercial banks.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 257-262